PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA MIND MAPPING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Siti Nurjanah; Ati Sadiah; Iis Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The main problem in this study is the low learning outcomes of students in economics subjects. This study aims to determine the influence of the application of the Jigsaw-type cooperative learning model with the help of Mind Mapping media. The research method used is a quasi-experimental method with a quantitative approach. The data collection technique was carried out through pretest and posttest The samples were taken using the purposive sampling technique, obtained from class XI IPS 4 as the experimental class and class XI IPS 2 as the control class. The data analysis technique uses paired sample t-test and independent sample t-test. The results of hypothesis testing showed: (1) There was an increase in student learning outcomes in the experimental class (2) There was an increase in student learning outcomes in the control class (3) There was a difference in the increase in learning outcomes between the experimental class and the control class, where the average n-gain value of the experimental class was higher than that of the control class, which was 0.67 and 0.57. Thus, it can be concluded that the use of a Jigsaw-type cooperative learning model with the help of Mind Mapping media can improve student learning outcomes.